STUDI KELAYAKAN KAJIAN AKADEMIS PENINGKATAN STATUS PUSKESMAS RAWAT INAP PALARAN MENJADI RUMAH SAKIT KELAS D PALARAN - Suman Yuga Utama; Lamri Lamri; Supriadi Supriadi; Rahmad Bahtiar; Syahrani Syahrani; Isnawati Isnawati (Jurnal Riset Inossa, 2021)
The increase in population encourages the government to meet the needs in the health sector. In line with this description, the government has developed the Palaran Public Health Center to become a Type D Hospital. Another impact of population growth is the government's ability to provide employment, which is increasing every year. With the investment in the construction of hospitals, it will be able to add new job fields. Rapid population development, such as in the city of Samarinda, demands an additional level of health services at a balanced pace. The Type D Palaran General Hospital is a combination of social and economic services with the development and addition of health services to government facilities. In solving the problem of equity and improving health services, the Type D Palaran General Hospital belongs to the Samarinda City Government, which is legally under the management of the Samarinda City Public Health Office. Based on the policy direction of the 2005-2025 RPJPD of Samarinda City regarding Strengthening the Comprehensive Development of Samarinda as well as the Strategic Plan of the Regional Research and Development Agency of the City of Samarinda for 2016-2021 regarding the Feasibility of Increasing the Status of the Palaran Inpatient Health Center to a Type D Hospital with the provisions as stated in Article 7 paragraph (1) that hospitals must meet requirements related to location, buildings, infrastructure, human resources, pharmaceuticals, equipment, environmental safety and spatial planning as well as Regulation of the Minister of Health Number 3 of 2020 concerning Hospital Classification and Licensing states that hospitals are health service institutions that provide complete individual health services that provide inpatient, outpatient, and emergency services.